Singlejet fluidized beds: experiments and CFD simulations with glass and polypropylene particles - Utikar, Ranjeet P.; Ranade, Vivek V. (Chemical Engineering Science, 2007)
Understanding hydrodynamics of bubbling fluidized beds is crucial in proper design and scale up of these beds. CFD models have shown promise in gaining this understanding. In order to generate confidence in CFD models, predicted time averaged and dynamical characteristics of the bubbling fluidized beds need to be validated against experimental data. This paper describes such studies with rectangular fluidized beds operated with a central jet. Digital image analysis and analysis of wall pressure fluctuations were used for this characterization. Fluidization of two types of particles, glass and polypropylene (PP) was studied at two different initial bed heights of H/D = 1 and 2 with three central jet velocities 5, 10 and 20 m/s. Time averaged as well as dynamical characteristics were studied. The Eulerian-Eulerian two fluid model based on kinetic theory of granular flows was used to simulate these experiments. The predicted results were compared with the experimental data and previously published correlations. Although, there is agreement with experimental data in some aspects, complete agreement was not found. The presented experimental data and comparison with CFD predictions will provide useful basis for further work on understanding bubbling fluidized beds. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: CFD; fluidized beds; hydrodynamics; image analysis; pressure fluctuations; single jet

Solid suspension and liquid phase mixing in solid-liquid stirred tanks - Sardeshpande, Madhavi V.; Sagi, Aparna R.; Juvekar, Vinay A.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2009)
Stirred tanks are widely used in chemical process industries for catalytic reactions, dissolution of solids, crystallization, and so oil. In designing and optimizing such processes, suspension quality Of Slurry is an important parameter. Suspension quality depends upon complex interactions of impeller generated flow, turbulence, and solid loading. Most of the earlier work on solid suspension focuses Oil identifying critical impeller speed for just suspension of solids (N(js)). In this study, apart from N(js) aspects like cloud height and liquid phase mixing in solid-liquid suspensions were also studied A new way of characterizing solid-liquid suspensions and liquid phase mixing using nonintrusive wall pressure fluctuation measurements has been developed. Systematic experimental data on N(js), cloud height, power consumption, mixing time, and circulation time over a range of solid volume fraction and impeller speeds have been presented here. The results and discussion presented here will have useful implications for designing solid-liquid stirred tanks.

Solid suspension in stirred tanks: UVP measurements and CFD simulations - Sardeshpande, Madhavi V.; Juvekar, Vinay A.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
Suspension of solids in stirred reactor is widely used for catalytic reactions, dissolution, etc. Quality of solid suspension is an important parameter required for the reliable design, optimum performance, and scale up of the system. Quality of suspension depends on local characteristics of solid velocity and hold up profiles. The present work was focused on investigating quality of solid suspension using ultrasound velocity profiler (UVP) measurements and CFD simulations. The slip velocity measurements carried out with UVP were used to evaluate different drag correlations used in CFD simulations. Results discussed in this work would be useful for extending the applications of CFD models for simulating large stirred slurry reactors.
Keywords: CFD; drag coefficient; solid suspension; solid-liquid velocities; UVP

Simulation of settling of solid particles due to sudden impeller stoppage - Sardeshpande, Madhavi V.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2012)
Stirred tank reactors (STRs), which are used in process industries (for a variety of operations, such as catalytic reactions, dissolution of a solid, crystallization, and so on), often involve handling of solid liquid (gas) systems. The solid suspension and the quality of the suspension are key issues in the design and operation of such stirred reactors. Despite extensive experimental work over previous decades, comprehensive understanding and reliable methods to predict the solids suspension and the quality of the suspension are not yet available. Advances in computational fluid dynamics (CFD) and new experimental techniques offer potentially effective ways of understanding solids suspension in stirred tanks. The present work highlights the potential of using transient measurements by way of the dynamic settling of solid particles because of the sudden stoppage of an impeller to evaluate CFD models. Sudden impeller stoppage results in significantly different conditions, in terms of the ratio of particle diameter to Kolomogorov length scale (d(p)/lambda), as well as the solids volume fraction experienced by solid particles. Therefore, experimental data under such sudden impeller stoppage offer a better way to evaluate the influence of prevailing turbulence and solids volume fraction on effective drag and therefore offer a more-stringent test to CFD models than steady-state profiles. Besides facilitating the development of computational models, the experimental and simulation studies of sudden impeller stoppage also provide useful data to gain insight into the behavior of the stirred tank after abrupt impeller stoppage due to sudden power failure.

Selectivity engineering of the diazotization reaction in a continuous flow reactor - Shukla, C. A.; Kulkarni, Amol A.; Ranade, Vivek V. (Reaction Chemistry & Engineering, 2016)
In situ generated diazonium salts are useful intermediates for the synthesis of fine chemicals and active pharmaceutical ingredients. This paper presents a methodology for selectivity engineering of the diazotization reaction in a continuous reactor. The yield of diazotization was found to depend on mixing, dispersion, reaction kinetics, operating temperature and residence time. Initially, experimental data and an isothermal axial dispersion model were used for estimating mixing time. A correlation for estimating mixing time for different flow reactors is proposed. The model predictions were compared with the experimental data. The validated axial dispersion model and Central Composite Design (CCD) were used to optimize diazotization in a straight tube reactor (1.78 mL). The model was then used for scaling-up of aniline diazotization from a straight tube reactor to a proprietary AmAR3 reactor (scale-up ratio of ∼20). The initial concentration, inlet temperature, average heat capacity of the reaction mixture, mixing, residence time (distribution) and available heat transfer area per unit volume of the reactor were found to be the key parameters for scaling-up of the diazotization reaction. The presented approach and results will be useful to practicing chemists and engineers for enhancing the selectivity of diazotization reactions in continuous reactors.

Solvent degradation studies using hydrodynamic cavitation - Suryawanshi, Pravin G.; Bhandari, Vinay M.; Sorokhaibam, Laxmi Gayatri; Ruparelia, Jayesh P.; Ranade, Vivek V. (Environmental Progress & Sustainable Energy, 2018)
Hydrodynamic cavitation for the degradation of organic solvents was investigated in detail using a newer form of cavitating device-vortex diode. The results were also compared with that using conventional cavitating device orifice. Removal of three different organic solventsacetone, methyl ethyl ketone (MEK), and toluene were studied on a pilot plant with capacity of 1m(3)/h. The effect of different operating parameters such as inlet pressure, initial concentration, and reactor type on the degradation rate of solvent was investigated in detail. The results revealed that efficiency of solvent removal varies substantially with the change in physical operating conditions and nature of the solvent. It was found that up to 80% degradation could be achieved for toluene (cavitational yield 32.2 x 10(-3) mg/J), substantially higher than that for acetone and MEK indicating the effect of molecular weight/structure in the degradation process. Further, the results clearly indicated chemical oxidation as a predominant mechanism for degradation and not physical destruction. Vortex diode that works on the principle of vortex generation for cavitation, was found to be far superior over conventional cavitating device-orifice- approximate to up to eight times higher cavitational yield could be obtained for toluene as compared to orifice. The results of this study provide newer insight into solvent removal using hydrodynamic cavitation and would have bearing on the treatment of solvent containing wastewaters. (C) 2017 American Institute of Chemical Engineers
Keywords: Effluent treatment; industry; pollution; Vortex diode; wastewater

Safe water and technology initiative for water disinfection: application of natural plant derived materials - Mane, Maya B.; Bhandari, Vinay M.; Ranade, Vivek V. (Journal of Water Process Engineering, 2021)
Safe drinking water is the necessity of life. The present study reveals use of natural resources such as plant extracts and natural oils for water disinfection. Differences between oil and water soluble additives were highlighted for plant extracts and insoluble natural oils. A hybrid hydrodynamic cavitation process was quite effective in both the cases and high rates of disinfection were achieved. Studies were reported using oils (ginger, turmeric, lavender, tulsi) and rhizome derived plant extracts such as ginger, turmeric and mango ginger, as additives in process intensification (0.1% v/V). A vortex based cavitation device (vortex diode, nominal capacity 1 m3/h) was used with pressure drop of 1 bar. A high disinfection of 96% and 88% was obtained in 15 min for ginger oil and mango ginger extract respectively as compared to 44% using cavitation alone. Acoustic cavitation gave 94% and 30% disinfection with and without additive-mango ginger extract. The FTIR analyses before and after cavitation, with ginger additive, showed no by-products formation and indicated gingerol as active component in disinfection. The per-pass disinfection values were also higher, up to 5 times than cavitation alone. Hybrid hydrodynamic cavitation using natural plant derived materials can offer a promising technology alternative in water disinfection.
Keywords: Cavitation; Disinfection; Natural oil; Plant extract; Water treatment